Combining Protein Ligation Systems to Expand the Functionality of Semi-Synthetic Outer Membrane Vesicle Nanoparticles - van den Berg van Saparoea, H. Bart; Houben, Diane; Kuijl, Coen; Luirink, Joen; Jong, Wouter S. P. (Frontiers in Microbiology, 2020)
Bacterial outer membrane vesicles (OMVs) attract increasing interest as immunostimulatory nanoparticles for the development of vaccines and therapeutic agents. We previously engineered the autotransporter protein Hemoglobin protease (Hbp) into a surface display carrier that can be expressed to high density on the surface of Salmonella OMVs. Moreover, we implemented Tag-Catcher protein ligation technology, to obtain dense display of single heterologous antigens and nanobodies on the OMVs through coupling to the distal end of the Hbp passenger domain. Here, we aimed to further expand the versatility of the Hbp platform by enabling the coupling of heterologous proteins to internal sites of the Hbp passenger. Inserted SpyTags were shown to be accessible at the Salmonella OMV surface and to efficiently couple SpyCatcher-equipped fusion proteins. Next, we combined distally placed SnoopCatcher or SnoopTag sequences with internal SpyTags in a single Hbp molecule. This allowed the coupling of two heterologous proteins to a single Hbp carrier molecule without obvious steric hindrance effects. Since coupling occurs to Hbp that is already exposed on the OMVs, there are no limitations to the size and complexity of the partner proteins. In conclusion, we constructed a versatile modular platform for the development of bivalent recombinant OMV-based vaccines and therapeutics.